HDL Cholesterol Subfractions and the Effect of Testosterone Replacement in Hypogonadism - Bolu, E.; Sonmez, A.; Tapan, S.; Taslipinar, A.; Aydogdu, A.; Meric, C.; Basaran, Y.; Uckaya, G.; Serdar, M.; Kurt, I.; Azal, O. (Hormone and Metabolic Research, 2013)
Metabolic disorders and cardiovascular events are increased in hypogonadism. Serum HDL composition is a better cardiovascular predictor than the HDL counts. However, there is no information about the HDL subfractions in patients with hypogonadism. We designed a prospective study to investigate the HDL subfractions in treatment naïve subjects with hypogonadism and the effects of 2 different testosterone replacement regimens on the HDL subfractions. Seventy young male patients with congenital hypogonadotropic hypogonadism (CHH) and 70 age and BMI-matched healthy males were enrolled in the present study. The patients were assigned to receive intramuscular injections of testosterone esters 250 mg every 3 weeks and transdermal testosterone applications 50 mg daily. Biochemical investigations including HDL subfractions and insulin resistance were done. Patients with CHH had higher levels of insulin, HOMA-IR, WC, triglyceride, and diastolic blood pressure. Although, the HDL cholesterol concentrations were similar in both groups, hypogonadal patients had lower HDL2 and higher HDL3 levels. The total testosterone levels were independent determinants of the HDL2 subfractions. During the follow-up, a significant increase in the BMI and WC values and a significant decrease in the levels of total cholesterol, HDL cholesterol, and HDL3 were observed. No difference was present between the 2 treatment arms. These results show that patients with hypogonadism have unfavorable HDL compositions in addition to the other dysmetabolic features. However, testosterone replacement for about six months neither improves the metabolic problems nor the HDL composition. Mechanistic studies are warranted to better understand the cardiovascular effects of unfavorable HDL compositions in hypogonadism.
Keywords: hypogonadism; testosterone replacement therapy; HDL cholesterol subfractions